2017
DOI: 10.1177/0033354916689611
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Nicotine Delivery Systems and Smoking Cessation in Arkansas, 2014

Abstract: Objectives: As of October 2015, evidence needed to make a recommendation about the use of electronic nicotine delivery systems (ENDS) for smoking cessation was limited. We used the 2014 Arkansas Behavioral Risk Factor Surveillance System with additional state-specific questions to determine the prevalence of ENDS use, the impact of ENDS use on smoking cessation, and beliefs about ENDS use in Arkansas. Our objectives were to determine if (1) ENDS use was associated with lower odds of quitting smoking, (2) ENDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
2
5
0
2
Order By: Relevance
“…In this study population of a low-risk pregnancy clinic, consisting of low-income pregnant women residing in an ethnically diverse population, we estimated a 6.8% prevalence for current ENDS use during pregnancy. This is consistent with the 6.1% estimate of current ENDS-using adults from the 2014 Arkansas BRFSS 33 and a national study of pregnant women 1 . Consistent with the latter source, we also found that 75.0% of ENDS users were current cigarette smokers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study population of a low-risk pregnancy clinic, consisting of low-income pregnant women residing in an ethnically diverse population, we estimated a 6.8% prevalence for current ENDS use during pregnancy. This is consistent with the 6.1% estimate of current ENDS-using adults from the 2014 Arkansas BRFSS 33 and a national study of pregnant women 1 . Consistent with the latter source, we also found that 75.0% of ENDS users were current cigarette smokers.…”
Section: Discussionsupporting
confidence: 86%
“…The Behavioral Risk Factor Surveillance System (BRFSS) estimated the prevalence of smoking in adults in Arkansas to be 24.8% in 2014, among the highest in the nation 31,32 . Given the high-risk for ENDS use, we had analyzed data from the Arkansas BRFSS on ENDS use and found that 6.1% of adults reported using ENDS within the past month 33 . Considering highly relevant a study to describe the prevalence of current ENDS use in pregnant women, we aim to: 1) assess the validity of self-reported ENDS use and cigarette smoking using salivary cotinine, exhaled carbon monoxide (CO), and hair nicotine as gold-standards; 2) examine the association of ENDS use during pregnancy with birth weight and the risk of SGA; and 3) reassess the association with the risk of SGA correcting for misclassification by self-report of tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…The GM for nicotine in hair samples of pregnant smokers are in agreement with reports of studies that examined nicotine in the hair of non-pregnant smokers 38 . Surprisingly, instead of observing lower levels of nicotine in dual ENDS users in our population of pregnant women, we found that nicotine, cotinine, NNK, and NNAL levels, in hair samples of dual users were consistently higher (although not statistically significantly higher) than those in hair samples of smokers.…”
Section: Discussionsupporting
confidence: 89%
“…The introduction and marketing of ENDS has changed the method of delivery and behaviors involved in nicotine consumption, adding a layer of complexity to the study of tobacco use 37 . Social media marketing of ENDS often promotes these devices as ‘safer’ than regular cigarettes, and often claims are made that ENDS ‘aid’ smoking cessation 38 . A higher percentage of current smokers than non-smokers in Arkansas believe they can reduce the harmful effects of smoking by switching or substituting cigarettes with ENDS 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation